HUBUNGAN PENGALAMAN DENGAN MOTIVASI IBU DALAM MEMBERIKAN IMUNISASI DPT 2 DI DESA PAYUDAN DUNG-DANG KECAMATAN GULUK-GULUK KABUPATEN SUMENEP TAHUN 2015 - Iva Gamar Dian Pratiwi (Wiraraja Medika : Jurnal Kesehatan, 2016)
National targets stipulate that the immunization targets is equal 95%, but in fact the coverage of DPT 2 in the village of Dang Dung- Payudan UPT Puskesmas working area Guluk-Guluk ie 62.5% of the target of 95% by 2014. The aim of this study was to determine the relationship experience with maternal motivation in giving DPT 2 ,The study design used was analytic correlational approach cross sectional study, the population of Capital in the village Payudan Dung-Dang 45 respondents, by using total sampling technique, the independent variable experience Mother, the dependent variable Motivation mother in giving DPT 2, data collection used questioner form and use spearmen test with significance level α = 0.05.The results showed that nearly half (42.2%), ie 20 people have less experience, and almost half (42.2%), ie 20 people have weak motivation. Spearman test analysis results show the value (ρ) = 0,000 and α = 0,05dengan thus ρ <α so that Ho refused meaning there is a relationship between experience with maternal motivation in giving DPT 2.It can be concluded that almost half the mothers in the village of Dang 2014 Payudan Dung- have experience DPT 2 less and almost half the mothers in the village payudan Dang Dung-2014 has a weak motivation in bringing their children to be immunized, Therefore to overcome this is by improving public knowledge about immunization, through education and counseling about the benefits of immunization, immunization side effects and how to handle.Keyword: experience, maternal motivation, immunization DPT2